2014
DOI: 10.1002/art.38279
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Luminescence Imaging of NF‐κB Activity and Serum Cytokine Levels Predict Pain Sensitivities in a Rodent Model of Osteoarthritis

Abstract: Objective To investigate the relationship between NF-κB activity, cytokine levels, and pain sensitivities in a rodent model of osteoarthritis (OA). Method OA was induced in transgenic NF-κB luciferase reporter mice via mono-iodoacetate (MIA) intra-articular injection. Using luminescent imaging we evaluated the temporal kinetics of NF-κB activity and its relationship to the development of pain sensitivities and serum cytokine levels in this model. Results MIA induced a transient increase in joint-related NF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 40 publications
(64 reference statements)
4
42
0
Order By: Relevance
“…Longitudinal images of the animal hind limbs were taken immediately following injection and up to 120 h after injection. To analyze the intensity of fluorescence emitted from the knee joint of each animal, a circular region of interest (ROI) was selected in the area of the knee comprising the intra-articular space and centered on the location of peak fluorescence in each image; the ROI was held constant in shape and size across all images and time points (Bowles et al 2013). The total fluorescence within the ROI for each animal at each time point was normalized to the total fluorescence measured at 2 h after injection, as this was the time of peak intra-articular fluorescence (total normalized fluorescence, T NF ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Longitudinal images of the animal hind limbs were taken immediately following injection and up to 120 h after injection. To analyze the intensity of fluorescence emitted from the knee joint of each animal, a circular region of interest (ROI) was selected in the area of the knee comprising the intra-articular space and centered on the location of peak fluorescence in each image; the ROI was held constant in shape and size across all images and time points (Bowles et al 2013). The total fluorescence within the ROI for each animal at each time point was normalized to the total fluorescence measured at 2 h after injection, as this was the time of peak intra-articular fluorescence (total normalized fluorescence, T NF ).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we explored the utility of silk fibroin microparticles developed for intra-articular drug delivery of small-molecule drugs by adapting the method for silk microparticle fabrication to incorporate conjugation of a fluorescent dye. In vitro studies of fluorophore release and measures of the intra-articular clearance of fluorophore from rat knee joints using live-animal, fluorescence in vivo imaging (Bowles et al 2013, Whitmire et al 2012), were performed to assess the potential for the silk microparticles to contribute to sustained release in this application.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that NF-κB signaling pathway plays an important role in degeneration of cartilage structure [9], together with the recent report that naringin antagonized activation of NF-κB signaling, led us to examine whether the interaction of naringin and NF-κB signaling is involved in protection of cartilage degeneration. For this purpose, primary murine chondrocyte was cultured in stimulation of TNF-α for 12 or 72 h, followed by real-time PCR and Western blot, respectively.…”
Section: Pgrn Inhibits Activation Of Nf-κb Signaling Pathway Both In mentioning
confidence: 99%
“…It has been reported that TNF-α plays a detrimental role and serves as a potential target in OA [8]. Moreover, NF-κB signaling is well accepted for cartilage destruction and exaggeration of OA [9]. It is known that naringin suppresses TNF-α function and antagonizes NF-κB signaling pathway in various conditions [10], but the role of naringin in cartilage degradation and OA progression remains unknown.…”
Section: Introductionmentioning
confidence: 98%
“…In addition to epigenetic changes, it is also clear that chronic and low-grade inflammation is involved in the progression of OA (5356) that leads to catabolic responses in chondrocytes via upregulation of factors such as nuclear factor-kappa B (NF-κB) (57), MMPs, and markers of chondrocyte hypertrophy (e.g., Col10a1 , Mmp13 , Runx2 , Alp ). Recent investigations from human patients as well as animal models suggest that the entire synovial joint, including articular cartilage, subchondral bone, synovial tissue, ligament, and meniscus, contribute to the inflammation network.…”
Section: Epigenetic and Inflammatory Changes In Oamentioning
confidence: 99%